Prophylaxis against spontaneous bacterial peritonitis: Too much or too little?. Issue 1 (17th June 2022) - Dhanani, Muhammad; Krishnamoorthy, Aparna; Ciolino, Jody D.; Gupta, Kalpana; Strymish, Judith M.
Abstract: Prophylaxis against spontaneous bacterial peritonitis (SBP) is recommended for select patients with cirrhosis, but long-term antibiotic therapy has risks. We evaluated concordance with guideline recommendations in 179 veterans with cirrhosis; 55% received guideline-concordant management of SBP prophylaxis. Despite stable guideline recommendations since 2012, guideline adherence remains low.